2018
DOI: 10.1080/15257770.2017.1421765
|View full text |Cite
|
Sign up to set email alerts
|

A convenient solid phase approach to obtain lipophilic 5′-phosphoramidate derivatives of DNA and RNA oligonucleotides

Abstract: This paper explores the potential of a modified phosphotriester approach to the synthesis of 5'-phosphoramidate derivatives of DNA and RNA oligonucleotides. The modification of 5'-deprotected support-bound oligonucleotides is done in two steps: i) conversion of the 5'-OH group of an oligonucleotide into an activated phosphodiester, and ii) treatment of the activated phosphodiester with an aminocompound. The approach is efficient and compatible with conventional solid phase oligonucleotide synthesis. It can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…We also showed that the formation of mono conjugates requires the removal of activating agents (Ph 3 P/(PyS) 2 /DMAP) and the three-fold washing of the support with the attached oligonucleotide before coupling with the amino-containing ligand. The treatment by an aqueous solution of methylamine or its mixture with ammonia to remove the protective groups and cleave the oligonucleotide from the polymer carrier did not destroy the P-N-bond [ 19 , 20 , 24 ]. In our work, we used an aqueous solution of methylamine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also showed that the formation of mono conjugates requires the removal of activating agents (Ph 3 P/(PyS) 2 /DMAP) and the three-fold washing of the support with the attached oligonucleotide before coupling with the amino-containing ligand. The treatment by an aqueous solution of methylamine or its mixture with ammonia to remove the protective groups and cleave the oligonucleotide from the polymer carrier did not destroy the P-N-bond [ 19 , 20 , 24 ]. In our work, we used an aqueous solution of methylamine.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the authors of [ 22 , 23 ] obtained a phosphoramide bond through the Staudinger reaction between azidoalkyl-modified lipophilic molecules and an internucleoside 2-cyanoethylphosphite of the polymer-bound protected oligonucleotide, which is formed at the condensation stage in a standard automated synthesis. Dovydenko et al [ 24 ] proposed a variant of the solid-phase phosphotriester approach: the active 5′-arylphosphodiester derivative reacted with the polymer-bound protected oligonucleotide, with the subsequent replacement of the azole moiety by an alkyl amine.…”
Section: Introductionmentioning
confidence: 99%